New directions in organizational behaviour? - Albert Martin (Management Revue, 2004)
Organizational behaviour research possesses some endemic problems which constrict its progress. This introduction to Management Revue's special issue on organizational behaviour debates six deficiencies in the current research: an unclear conception of how to understand the 'organizational' in organizational behaviour; the lack of studies which connect micro- and macro-behaviour; a sterile concentration on the study of relationships instead of mechanisms; a superficial understanding of the practical side of organizational behaviour research; an ignorance of the upheavals in the world of work; and a stagnation in theoretical developments. The last section introduces other articles in this issue of Management Revue.
Keywords: 650; organizational behaviour; micro-macro link; behavioural mechanisms; praxeology; Organisationsforschung; Verhalten in Organisationen